Recommendations for postoperative radiotherapy in head & neck squamous cell carcinoma in the presence of flaps: A GORTEC internationally-reviewed HNCIG-endorsed consensus. (July 2021) - Carsuzaa, Florent; Lapeyre, Michel; Gregoire, Vincent; Maingon, Philippe; Beddok, Arnaud; Marcy, Pierre-Yves; Salleron, Julia; Coutte, Alexandre; Racadot, Severine; Pointreau, Yoann; Graff, Pierre; Beadle, Beth; et al.
Highlights: Our GORTEC internationally-reviewed consensus showed that the flap-tissue junction should be considered at higher risk of tumor spread compared to other areas of the flap. Surgeons should report the placement of flaps more accurately and consider clip placement to guide radiotherapy planning. The risks of radiation-induced atrophy, fibrosis, and osteoradionecrosis should be considered during radiotherapy optimization. Abstract: Introduction: Head and neck reconstructive surgery using a flap is increasingly common. Best practices and outcomes for postoperative radiotherapy (poRT) with flaps have not been specified. We aimed to provide consensus recommendations to assist clinical decision-making highlighting areas of uncertainty in the presence of flaps. Material and methods: Radiation, medical, and surgical oncologists were assembled from GORTEC and internationally with the Head and Neck Cancer International Group (HNCIG). The consensus-building approach covered 59 topics across four domains: (1) identification of postoperative tissue changes on imaging for flap delineation, (2) understanding of tumor relapse risks and target volume definitions, (3) functional radiation-induced deterioration, (4) feasibility of flap avoidance. Results: Across the 4 domains, international consensus (median score ≥ 7/9) was achieved only for functional deterioration (73.3%); other consensus rates were 55.6% for poRT avoidance of flap structures, 41.2% for flap definition and 11.1% for tumor spread patterns. Radiation-induced flap fibrosis or atrophy and their functional impact was well recognized while flap necrosis was not, suggesting dose-volume adaptation for the former. Flap avoidance was recommended to minimize bone flap osteoradionecrosis but not soft-tissue toxicity. The need for identification (CT planning, fiducials, accurate operative report) and targeting of the junction area at risk between native tissues and flap was well recognized. Experts variably considered flaps as prone to tumor dissemination or not. Discrepancies in rating of 11 items among international reviewing participants are shown. Conclusion: International GORTEC and HNCIG-endorsed recommendations were generated for the management of flaps in head and neck radiotherapy. Considerable knowledge gaps hinder further consensus, in particular with respect to tumor spread patterns.